Sistem Informasi Pendaftaran Siswa Baru Berbasis Web pada MA Futuhiyah Jeketro - Syifa Nur Hanna; Rony Wijanarko (Universitas Wahid Hasyim, 2023)
The need for communication and information today in a school infrastructure is very necessary. One of them is the school registration information system to make it easier to access information to all prospective new students. So it is necessary to use information technology to improve quality, efficiency and productivity for education management. This system was created using the waterfall method and the PHP programming language, and MYSQL as the database server. So that this system will make the process of data collection and administration easier and faster. Thus it can provide benefits in time efficiency and also energy.